Advanced Merkel cell carcinoma of the lower extremity treated with surgery and isolated pelvic and limb perfusion using Melphalan: A case of unexpected long-term survival. (2019) - Guadagni, S.; Chiominto, A.; Mackay, A.R.; Farina, A.R.; Cappabianca, L.; Puccica, I.; Valiyeva, S.; Clementi, M.
Highlights: Merkel cell carcinoma is a rare and aggressive skin cancer. We report the case of a female patient with recurrent MCC of the leg. The patient was not eligible for immunotherapy, systemic chemotherapy and radiotherapy. The patient received repeated surgical excisions combined with Melphalan IPLPs with unexpected long-term survival. Abstract: Introduction: Merkel cell carcinoma (MCC) is a rare, neuroendocrine skin tumor, with high frequency of locoregional recurrence, metastases, and poor prognosis. Locoregional MCC recurrence in the extremities can pose considerable treatment challenges. We report a case of long-term survival in a female patient with recurrent MCC of the leg, treated with surgery and locoregional chemotherapy. Presentation of case: A 73-year-old female with cirrhosis and hepatitis C, developed cutaneous MCC in the left inferior limb. This patient initially received surgical treatment, with subsequent negative sentinel lymph-node biopsy in another center, one-month prior recovery in our department, and arrived with 4 new limb nodules, cranially to the previously treated area, without distant metastases or inguinal lymph node recurrence. This patient was not eligible for immunotherapy due to active hepatitis upon treatment with NS5B inhibitors, or eligible for systemic chemotherapy or radiotherapy due to severe neutropenia and was, therefore, subjected to surgical resection combined with Isolated Pelvic and Limb Perfusion (IPLP) with Melphalan. Histological evaluation confirmed MCC diagnosis and during the following 4 months, she developed further locoregional recurrences with homolateral inguinal lymph node involvement and was subjected to two additional rounds of surgery plus IPLP. Discussion: All procedures were tolerated, systemic toxicities were temporary and subsequent clinical and radiological follow-up, following the last combined treatment, indicated that this patient was still alive and disease-free, at 56 months. Conclusion: In this case, surgery combined with locoregional Melphalan chemotherapy was an effective and repeatable treatment for recurrent MMC and resulted in unexpected long-term survival.